MANAJEMEN PEMBELAJARAN TAHFIDZ ALQURAN DI SEKOLAH - Candra Wijaya; Yusnaili Budianti; Fauzan Yusuf Helmi (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2022)
Abstract: This research article aims to find out how is the management of Tahfidz Al-Qur'an learning in schools? This research uses qualitative research. The approach used in this study is a naturalistic qualitative that was carried out at the Al-Fityah Binjai Foundation which includes Al-Fityah Elementary School, Junior School and High School. This approach is carried out by making a systematic and objective description of events, by collecting, evaluating, verifying, and synthe-sizing evidence to support the facts in order to obtain a conclusion. The results showed that the management of Tahfidz Al-Qur'an learning in schools was carried out through empathy, namely 1) Learning planning, where the implementation was arranged by involving the foundation and the school, Tahfiz Al-Qur'an learning planning contained subject matter, learning media, learning methods and time assessment. 2) Organizing learning which is carried out through the division of teaching tasks and the formation of a curriculum deve-lopment team that is oriented to the process of deter-mining, grouping, determining authority and respon-sibility by policy makers. 3) The imple-mentation of tahfidzul quran learning is carried out on the basis of four things, namely the material for each meeting, methods, class management, and teaching and learning activities. 4) evaluation of tahfidzul quran learning in these three schools was car-ried out using formative evaluation and summative evaluation.Keywords: Management, Learning, Ta